An Assessment of Demersal Elasmobranch Occurrence and Associated Habitats Using an Autonomous Underwater Vehicle ( AUV ) - Jonathon Taylor; John A. Howe; James Thorburn; Clive J. Fox; Christopher McGonigle; Petra Rybanska (Marine Ecology, 2025)
To implement effective management and conservation strategies, an understanding of the spatial ecology, habitat preferences and movement of demersal elasmobranchs is required. This study combines a photographic survey obtained from an autonomous underwater vehicle (AUV) with existing bathymetric data to help understand elasmobranch ecology within the Firth of Lorn, western Scotland. This area is within the Loch Sunart to Sound of Jura Marine Protected Area (MPA) and designated for the protection of the critically endangered flapper skate ( Dipturus intermedius ). Two areas of seabed were surveyed using an AUV in water depths of 110–165 m southwest of the Isle of Kerrera. Eight surveys were conducted in total, four in each area. Each area was surveyed twice over 2 days in October 2020 and twice in 2 days in May June 2021. One day used bait on the seabed (October) whilst all the others had no bait. For each survey, the AUV travelled 17 km at a height of 2 m above the seabed in a lawnmower pattern providing 0.5 km 2 photographic coverage for ~2 h per survey. Five elasmobranch species, two scyliorhinids ( Scyliohinus canicula and Galeus melastomus ) and three rajiformes ( D. intermedius , Raja clavata and Leucoraja naevus ), were identified from a total of 43 k seabed photographs. In total 42 individual animals and 7 egg cases were observed. Although the AUV had short survey times and small study areas the results are encouraging for AUVs being a useful tool in understanding elasmobranch ecology.